REGULARIZATION OF THE BOUNDARY–VALUE PROBLEM WITH MIXED CONDITIONS FOR A SECOND ORDER HYPERBOLIC EQUATION - Repetylo, S. M.; Hlynsky, Ya. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
A boundary value problem with data on the whole boundary of the domain for a linear homogeneous second-order hyperbolic equation with coefficients variable in spatial coordinates is considered. The issues of correct solvability and construction of a solution in the form of a series according to the system of orthogonal functions are studied. For the case when the right-hand sides of the boundary conditions are given with an error, a regularizing algorithm for the finding the approximate solution of the considered problem is constructed.